2014
DOI: 10.1371/journal.pone.0086166
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus-Induced Lung Inflammation Was Modulated by Cigarette Smoke Exposure in Mice

Abstract: Although smokers have increased susceptibility and severity of seasonal influenza virus infection, there is no report about the risk of 2009 pandemic H1N1 (pdmH1N1) or avian H9N2 (H9N2/G1) virus infection in smokers. In our study, we used mouse model to investigate the effect of cigarette smoke on pdmH1N1 or H9N2 virus infection. Mice were exposed to cigarette smoke for 21 days and then infected with pdmH1N1 or H9N2 virus. Control mice were exposed to air in parallel. We found that cigarette smoke exposure alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 55 publications
3
26
1
Order By: Relevance
“…Similarly, chronic CS exposure also increased MIP-2 and IL-6 at ZT6/12 when compared to controls. However, IL-6 and MIP-2 levels were dampened in CS plus Virus group which could be due to immunosuppressive effects of CS which is in line with recent report in which CS exposure suppressed the production of cytokines and chemokines after pandemic H1N1 or avian H9N2 virus infection in mice 57 . It has been shown that the IAV-mediated inflammatory response begins early on day 3 and remains high until day 5–7 post-infection 58 .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, chronic CS exposure also increased MIP-2 and IL-6 at ZT6/12 when compared to controls. However, IL-6 and MIP-2 levels were dampened in CS plus Virus group which could be due to immunosuppressive effects of CS which is in line with recent report in which CS exposure suppressed the production of cytokines and chemokines after pandemic H1N1 or avian H9N2 virus infection in mice 57 . It has been shown that the IAV-mediated inflammatory response begins early on day 3 and remains high until day 5–7 post-infection 58 .…”
Section: Discussionsupporting
confidence: 90%
“…Cell isolation and flow cytometry. Cells were isolated from the whole lung by digestion with collagenase and DNase as previously described by us (25). Cells obtained from the whole lungs, mLN, and spleen were washed and incubated with anti-mouse CD16/32 (BioLegend) for blocking.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency of the influenza infection was strikingly reduced in mice pretreated with LPS/elastase compared to naïve mice, as revealed by significantly lower viral titers at the peak of viral infection, day 5 and day 7 post infection ( Figure S2) which was also reflected by reduced amounts of viable virus in the lung on day 5 (data not shown). This is likely to be due to the development of a polyclonal antibody response observed upon LPS/elastase treatment ( [37,38] and data not shown). Thus, the response to the influenza infection was not comparable between LPS/elastase pretreated and naive mice, and was therefore not included in the remainder of the study.…”
Section: Influenza-induced Exacerbations Are Characterized By Neutropmentioning
confidence: 97%